Particular Candida albicans Strains in the Digestive Tract of Dyspeptic Patients, Identified by Multilocus Sequence Typing - Gong, Yan-Bing; Zheng, Jian-Ling; Jin, Bo; Zhuo, De-Xiang; Huang, Zhu-Qing; Qi, He; Zhang, Wei; Duan, Wei; Fu, Ji-Ting; Wang, Chui-Jie; Mao, Ze-Bin (PLOS ONE, 2012)
Background Candida albicans is a human commensal that is also responsible for chronic gastritis and peptic ulcerous disease. Little is known about the genetic profiles of the C. albicans strains in the digestive tract of dyspeptic patients. The aim of this study was to evaluate the prevalence, diversity, and genetic profiles among C. albicans isolates recovered from natural colonization of the digestive tract in the dyspeptic patients. Methods and Findings Oral swab samples (n = 111) and gastric mucosa samples (n = 102) were obtained from a group of patients who presented dyspeptic symptoms or ulcer complaints. Oral swab samples (n = 162) were also obtained from healthy volunteers. C. albicans isolates were characterized and analyzed by multilocus sequence typing. The prevalence of Candida spp. in the oral samples was not significantly different between the dyspeptic group and the healthy group (36.0%, 40/111 vs. 29.6%, 48/162; P > 0.05). However, there were significant differences between the groups in the distribution of species isolated and the genotypes of the C. albicans isolates. C. albicans was isolated from 97.8% of the Candida-positive subjects in the dyspeptic group, but from only 56.3% in the healthy group (P < 0.001). DST1593 was the dominant C. albicans genotype from the digestive tract of the dyspeptic group (60%, 27/45), but not the healthy group (14.8%, 4/27) (P < 0.001). Conclusions Our data suggest a possible link between particular C. albicans strain genotypes and the host microenvironment. Positivity for particular C. albicans genotypes could signify susceptibility to dyspepsia.